2019
DOI: 10.1101/752816
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Gene networks in cancer are biased by aneuploidies and sample impurities

Abstract: Gene regulatory network inference is a standard technique for obtaining structured regulatory information from, among other data sources, gene expression measurements.Methods performing this task have been extensively evaluated on synthetic, and to a lesser extent real data sets. They are often applied to gene expression of human cancers.However, in contrast to the evaluations, these data sets often contain fewer samples, more potential regulatory links, and are biased by copy number aberrations as well as cel… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 68 publications
0
3
0
Order By: Relevance
“…These can lead to spurious trans-eQTL signals, because genetic variants associated with cell type composition changes would appear as trans-eQTLs for cell-type-specific genes [3]. Furthermore, multiple studies have demonstrated that also the co-expression signals in tissues are largely driven by cell type composition effects [44][45][46]. Thus, even though PLIER detected the ARHGEF3 trans-eQTL in whole blood, this could have been at least partially driven by the change in platelet proportion between individuals [9].…”
Section: Discussionmentioning
confidence: 99%
“…These can lead to spurious trans-eQTL signals, because genetic variants associated with cell type composition changes would appear as trans-eQTLs for cell-type-specific genes [3]. Furthermore, multiple studies have demonstrated that also the co-expression signals in tissues are largely driven by cell type composition effects [44][45][46]. Thus, even though PLIER detected the ARHGEF3 trans-eQTL in whole blood, this could have been at least partially driven by the change in platelet proportion between individuals [9].…”
Section: Discussionmentioning
confidence: 99%
“…Classic methods that infer networks from multiple samples of unperturbed gene expression can roughly be divided in correlation-based and information-theoretic models. These and more methods have been reviewed in detail 8,10,28,29 and hence we only provide a brief overview. Information-theoretic approaches started out with relevance networks 12 , in which the pairwise mutual information (MI) is computed between all pairs of genes.…”
Section: Network Inference Methods Have Been Extensively Evaluated Onmentioning
confidence: 99%
“…CNV correction. As the presence of CNVs can influence and bias the generation of gene networks (Schubert et al, 2019), corto gives the optional possibility to use CNV data to correct target expression profiles via linear regression. An example of corto CNV-corrected network analysis in the TCGA Glioblastoma (GBM) dataset is provided in the package vignette and in Supp Figure S1 .…”
Section: Functionalitiesmentioning
confidence: 99%